2019
DOI: 10.1186/s40246-019-0201-y
|View full text |Cite
|
Sign up to set email alerts
|

The significance of trisomy 7 mosaicism in noninvasive prenatal screening

Abstract: Background This study was an evaluation of the role of noninvasive prenatal testing (NIPT) in the detection of trisomy 7 in prenatal diagnosis. Method A total of 35 consecutive cases underwent screening for trisomies by cell-free DNA testing between April 2015 and November 2017 due to suspicious NIPT results; these cases represented 0.11% of patients (35/31,250) with similar frequencies of abnormal results among the laboratories performing the tests. NIPT was offered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Nevertheless, a placental study was not always conducted in previous expanded NIPS studies; there were very few positive cases studied and confirmed in the placenta. The study by Qi Y et al included placenta examination in 8 of 29 cases with trisomy 7 alone; this is the largest case number of placenta studies for trisomy 7 screened positive cases up to date [ 17 ]. In our study, we also examined the placenta in three (of 14) cases in cohort 1; non-mosaic trisomy 7 in the placenta was identified in one case, which was confirmed with true fetal mosaicism by AF analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a placental study was not always conducted in previous expanded NIPS studies; there were very few positive cases studied and confirmed in the placenta. The study by Qi Y et al included placenta examination in 8 of 29 cases with trisomy 7 alone; this is the largest case number of placenta studies for trisomy 7 screened positive cases up to date [ 17 ]. In our study, we also examined the placenta in three (of 14) cases in cohort 1; non-mosaic trisomy 7 in the placenta was identified in one case, which was confirmed with true fetal mosaicism by AF analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, trisomy 7 identified in the CVS analysis was never confirmed by amniocentesis, suggesting the trisomic cells are most likely confined to the placenta [ 10 , 14 , 16 ]. In a recent genome-wide NIPS study by Qi Y et al, where 35 cases with positive trisomy 7 NIPS results were retrospectively reviewed [ 17 ], trisomy 7 was not confirmed in any cases who received the diagnostic testing by amniocentesis. Further investigations on 10 cases where the placenta was available indicated all these trisomy 7 NIPS-positive samples were placental mosaicism for chromosome 7 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the T7 case, the value of ε7ε was 0.24 (fetal fraction: 31.04 %). Based on other NIPT reports involving T7, it was most likely due to mosaicism. Three cases of T21 including two singletons and one twin were confirmed by karyotyping (95% CI, 29.24%‐100.00%).…”
Section: Resultsmentioning
confidence: 88%
“…In addition, a recent study reported that NIPT performed well in detecting subchromosomal microdeletions/ microduplications with a large clinical sample size through this platform [8]. Moreover, we are exploring the detection of other chromosomal abnormalities using this platform [23]. However, NIPT is a screening test, and all the abnormal results underscore the need for additional validation before routine use in practice as well as the necessity for confirmatory diagnostic testing after a positive cfDNA result.…”
Section: Discussionmentioning
confidence: 99%